Characterization of the complete chloroplast genome of Poa pratensis L. cv. Qinghai (Gramineae). Issue 1 (2nd January 2020) - Wei, Linna; Zhang, Chunping; Dong, Quanmin; Yu, Yang; Yang, Xiaoxia
Abstract: This study provides a chloroplast genome of Poa pratensis L. cv. Qinghai. The complete genome is 135, 606 bp in length with a G + C content of 38.28%, which contains 32 tRNA genes, and 8 rRNA genes. The phylogenetic analysis indicated that P. pratensis L. cv. Qinghai is closely related to Festuca arundinacea cultivar KY-31 . These results contribute to explore the genetic evidence for adaptation to the Qinghai-Tibet Plateau.